A model-driven approach to studying dissociations between body size mental representations in anorexia nervosa. (March 2017) - Moscone, Anne-Laure; Amorim, Michel-Ange; Le Scanff, Christine; Leconte, Pascale
Highlights: Dissociations between representation of body sizes for women with and without AN. CBS and BMI discrepancy for both groups followed a common linear continuum. The over-estimation of CBS was greater among the AN group than the control group. Body dissatisfaction was better explained by CBS for the AN group. Body dissatisfaction was better explained by BMI for the control group. Abstract: This study compared dissociations between mental representations of current, ideal and normal body sizes (i.e., Current BS, Ideal BS and Normal BS) for women with anorexia nervosa (AN group, n = 56) and healthy women (control group, n = 56). Along the lines of the single channel model of Cornelissen et al. (2013), the discrepancy between Current BS and BMI for both groups was adequately described along a common linear continuum of Current BS (mis)perception. Body size mental representations were ranked similarly (Ideal BS < Current BS < Normal BS) in each group. Whilst the over-estimation of Current BS was much greater among the AN group than the control group, body dissatisfaction was better explained by Current BS for the AN group and by BMI for the control group. Dissociation between Current BS and participants' BMI appears to be a key element when seeking to understand AN.